Accelerating learning performance of back propagation algorithm by using adaptive gain together with adaptive momentum and adaptive learning rate on classification problems - Abdul Hamid, Norhamreeza; Mohd Nawi, Nazri; Ghazali, Rozaida; Mohd Salleh, Mohd Najib (2011)
The back propagation (BP) algorithm is a very popular learning approach in feedforward multilayer perceptron networks. However, the most serious problem associated with the BP is local minima problem and slow convergence speeds. Over the years, many improvements and modifications of the back propagation learning algorithm have been reported. In this research, we propose a new modified back propagation learning algorithm by introducing adaptive gain together with adaptive momentum and adaptive learning rate into weight update process. By computer simulations, we demonstrate that the proposed algorithm can give a better convergence rate and can find a good solution in early time compare to the conventional back propagation. We use two common benchmark classification problems to illustrate the improvement in convergence time.